Multi-stakeholder collaboration in urban freight consolidation schemes: drivers and barriers to implementation - Paddeu, Daniela; Parkhurst, Graham; Fancello, Gianfranco; Fadda, Paolo; Ricci, Miriam (Transport, 2018)
Due to the motivations of climate change, the health impacts of poor air quality, and the importance of cities for economic growth, transport policy at all levels of governance places emphasis on reducing and managing urban traffic and congestion. Whilst the majority of urban traffic is created by personal travel, freight vehicles make a relatively large contribution per vehicle to congestion, pollution and severe accidents. The European Commission (EC 2011) estimates that 6% of all EU transport carbon emissions are from urban freight. For these reasons, a well-structured portfolio of measures and policies oriented towards more sustainable and efficient management of supply chain activities carried out in urban areas is needed, in order to reduce negative externalities related to urban mobility and improve economic performance. In recent years, there has been enthusiasm amongst commentators that shared-resource economic models can both create new commercial opportunities and address policy problems, including in the transport sector. Within the city logistics subsector, this new model is exemplified by the emergence of Urban freight Consolidation Centres (UCCs). UCCs replace multiple ‘last-mile’ delivery movements, many of which involving small consignments, by a common receiving point (the consolidation centre), normally on the periphery of a city, with the final part of the delivery being shared by the consignments in a small freight vehicle. Such arrangements can represent a good compromise between the needs of city centre businesses and their customers on the one hand (i.e. high availability of a range of goods) and local and global sustainability objectives on the other. At the same time, by sharing logistics facilities and delivery vehicles, UCCs offer added-value services to both urban economic actors, such as retailers, and network logistics providers. However, UCCs add to the complexity of logistics chains, requiring additional contracts, communications and movement stages. These arrangements also introduce additional actors within the supply of delivery services, notably local authorities present as promoters and funders, rather than simply as regulators, companies specialised in the UCC operation, and companies, which provide specialist technologies, such as electric delivery vehicles. UCCs therefore also represent an example of multi-stakeholder collaboration. Drawing on the results of a 2013 survey in Bristol (United Kingdom) and a further survey carried out in 2015 in Cagliari (Italy), the present paper will provide an in-depth comparison of the differences in the perceptions of urban freight users and stakeholders towards UCCs. Retailers involved in the survey carried out in Bristol showed high satisfaction with the delivery service provided by the UCC. Different topic areas (e.g. timeliness, reliability, safety) are examined through analyses of both qualitative and quantitative data. The survey carried out in Cagliari investigated the inclination of potential users to join a UCC scheme. The comparison between the two cities considers factors such as the nature of business holding (e.g. SME versus multiple retailers), operational practices (e.g. pattern of deliveries) and operating subsector (e.g. food versus no food). An analysis on the barriers to the implementation of UCCs in Bristol and in Cagliari is provided at the end of the paper.